Salt backwashing of organic-fouled ultrafiltration membranes: Effects of feed water properties and hydrodynamic conditions. (August 2019) - Chang, Haiqing; Liu, Baicang; Yang, Ping; Wang, Qingyuan; Li, Kai; Li, Guibai; Liang, Heng
Graphical abstract: Highlights: Salt solution was used as backwash water to clean organic-fouled UF membranes. Backwash behavior of NaCl solution backwash and UF permeate backwash was compared. NaCl solution backwash outperform UF permeate backwash in HCE and HIFI. High HCEs of NaCl solution backwash were hardly affected by the parameters tested. Low HIFI of salt backwash depends on feed properties and hydrodynamic conditions. Abstract: In the application of ultrafiltration (UF) membranes, organics can result in severe hydraulically irreversible fouling which is not eliminated effectively by periodic backwashing. Using NaCl solution as backwash water, the effects of feed water properties and hydrodynamic conditions on irreversible fouling caused by humic acid and sodium alginate were systematically investigated. Results showed that NaCl solution backwashing resulted in high hydraulic cleaning efficiencies (HCEs) which were hardly affected by feed concentrations, ionic strengths, solution temperatures, filtration fluxes, backwash fluxes, and backwash intervals ( p > 0.05). An alleviated hydraulically irreversible fouling was observed at a low feed concentration, a low ionic strength, a high temperature, a small filtration flux, a large backwash flux, a long backwash duration, and a short backwash interval. Using a constant backwash volume, all the multiple backwash parameters of NaCl solution backwashing led to high and comparable HCEs (∼97%), and the HIFIs were equal statistically ( p > 0.05) for a fixed backwash duration or interval. Membrane charge and surface tension analysis suggested that NaCl solution backwashing outperformed UF permeate backwashing by restoring almost characteristics of UF membranes. Scanning electron microscopy observation further revealed the superiority of NaCl solution backwashing to UF permeate backwashing for alleviating organic fouling of UF membranes.